2015
DOI: 10.1080/15384047.2015.1026472
|View full text |Cite
|
Sign up to set email alerts
|

Bmi-1 expression modulates non-small cell lung cancer progression

Abstract: y These authors equally contributed to this work.Keywords: Bmi-1, EMT, invasion, metastasis, NSCLC, progression Abbreviations: NSCLC, non-small cell lung cancer; EMT, epithelial-mesenchymal transition; Bmi-1, B lymphoma Mo-MLV insertion region 1 homolog; IHC, immunohistochemistry; FBS, fetal calf serum; qRT-PCR, quantitative real-time PCR.Previous studies indicate that the role of B lymphoma Mo-MLV insertion region 1 homolog (Bmi-1) is responsible for multiple cancer progression. However, Bmi-1 in controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…It has also been reported that BMI-1 repression induces epithelialmesenchymal transition and progression of lung cancer in vitro. In our study, overall survival in lung squamous cell carcinoma was inversely correlated with BMI-1 expression, and these results were supported by a previous report (18). In another report, BMI-1 mRNA expression in early stage breast cancer was higher than in late stage and was inversely related with lymph node metastasis (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has also been reported that BMI-1 repression induces epithelialmesenchymal transition and progression of lung cancer in vitro. In our study, overall survival in lung squamous cell carcinoma was inversely correlated with BMI-1 expression, and these results were supported by a previous report (18). In another report, BMI-1 mRNA expression in early stage breast cancer was higher than in late stage and was inversely related with lymph node metastasis (21).…”
Section: Discussionsupporting
confidence: 92%
“…These results suggested that BMI-1 may cause carcinogenesis in early events, but not late stage progression, but this remains controversial. Another study of BMI-1 expression in lung cancer showed significant correlation with early and decline in late stages of disease, which is negatively correlated with nodal involvement (18). They reported that silencing of BMI-1 expression induced invasiveness and metastasis in human lung cancer cell lines in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, accumulating evidence demonstrates that Bmi-1 is upregulated in malignant tumors and is correlated with disease progression [22][23][24]. In addition, it has been shown that Bmi-1 induces EMT, an important mechanism in the initial step of metastasis [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…B lymphoma Mo-MLV insertion region 1 homolog (BMI-1) is a component of polycomb repressive complex 1 (PRC1) (27). In NSCLC, BMI-1 has been demonstrated as an oncogene due to its functions in tumor proliferation, invasion and chemoresistance (28,29). In the present study, it was found that the expression of BMI-1 was downregulated by CCAT1 silencing in NSCLC cells.…”
Section: Discussionmentioning
confidence: 58%